2008
DOI: 10.1108/14013380810919840
|View full text |Cite
|
Sign up to set email alerts
|

Association between independent audit committee members' human‐resource features and underpricing

Abstract: Purpose -The primary objective of this paper is to examine the association between the seven human-resource features (spanning three major themes: qualifications and credentials; business and initial public offering (IPO) launch experience; and diversity) of independent audit committee members and the level of underpricing. Design/methodology/approach -A sample of 410 Singapore IPOs listing on the stock exchange of Singapore from January 1, 1997 to December 31, 2006 was used. Findings -Empirical results overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 84 publications
(102 reference statements)
2
12
1
1
Order By: Relevance
“…It shows that a higher issue price attenuates the prevailing information asymmetry and as put by Krishnamurti, Thong, & Vishwanath (2009), resulting in the higher issue price and subsequently lower underpricing. Age of the firm at the time of going public with loose statistical significance has a positive relation with underpricing similar to findings of Mitchell Van der Zahn, Singh, and Singh (2008) in Singapore and Hearn (2012) in sub-Saharan Africa. This shows that older the firm more the positive value associated with the market reflected in excess initial returns.…”
Section: Resultssupporting
confidence: 80%
“…It shows that a higher issue price attenuates the prevailing information asymmetry and as put by Krishnamurti, Thong, & Vishwanath (2009), resulting in the higher issue price and subsequently lower underpricing. Age of the firm at the time of going public with loose statistical significance has a positive relation with underpricing similar to findings of Mitchell Van der Zahn, Singh, and Singh (2008) in Singapore and Hearn (2012) in sub-Saharan Africa. This shows that older the firm more the positive value associated with the market reflected in excess initial returns.…”
Section: Resultssupporting
confidence: 80%
“…The positive relationship between underpricing and underwriter reputation has been documented in studies such as Beatty and Welch (1996), Mitchell Van der Zahn, Singh, and Singh (2008), Chahine and Tohmé (2009), Liu and Ritter (2011), Gao et al (2015), Thorsell and Issakson (2014). The explanation for positive relation is that reputed underwriters help in reducing the information asymmetry and uncertainty regarding the IPO.…”
Section: Review Of Literaturementioning
confidence: 78%
“…In contrast to Beatty and Ritter (1986), Johnson and Miller (1988), Reutzel and Belsito (2015), Dhamija and Arora (2017), Sundarasen et al (2018) which reported negative relationship and Beatty and Welch (1996), Mitchell Van der Zahn, Singh, and Singh (2008), Chahine and Tohmé (2009), Liu and Ritter (2011), Thorsell and Issakson (2014),Gao et al (2015), Alvarez-Otero and Lopez-Iturriaga (2018) which reported positive relationship between underwriter reputation and underpricing, various other studies such as Shin (2010), Tian (2012), Anderson, Chi, and Wang (2015), Velamuri and Liu (2017), Bhattacharya (2017), Badru and Ahmad-Zaluki (2018) reported insignificant relation between the two. In the context of our study in Indian setting in case of SMEs, the positive relation between underwriter reputation and underpricing has been hypothesized in present study.…”
Section: Review Of Literaturementioning
confidence: 88%
“…In line with the findings of Su and Fleisher (1999), issue price shares a negative relation with underpricing which means lower the issue price higher will be the listing day return. Firm age, though, shares an insignificant relation with adjusted underpricing, the non-negative coefficient is explained by Mitchell Van der Zahn, Singh, and Singh (2008) in Singapore and Hearn (2012) in Sub-Saharan Africa suggesting that investors highly value old firms having a long operating history as mature firms ameliorate fears of investors regarding its future performance.…”
Section: Sources Of Data and Research Methodologymentioning
confidence: 99%